2004
DOI: 10.1197/jamia.m1664
|View full text |Cite
|
Sign up to set email alerts
|

Will the Wave Finally Break? A Brief View of the Adoption of Electronic Medical Records in the United States

Abstract: For over thirty years, there have been predictions that the widespread clinical use of computers was imminent. Yet the "wave" has never broken. In this article, two broad time periods are examined: the 1960's to the 1980's and the 1980's to the present. Technology immaturity, health administrator focus on financial systems, application "unfriendliness," and physician resistance were all barriers to acceptance during the early time period. Although these factors persist, changes in clinicians' economics, more c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
109
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(116 citation statements)
references
References 17 publications
2
109
0
Order By: Relevance
“…With increasing computerisation in every sector of activity, ICTs are expected to become tools that are part of healthcare professional practice. Nonetheless, it appears that ICTs such as electronic medical records and the Internet remain underused by healthcare professionals (Berner 2005;Brooks 2006). Human and organisational factors have been identified as the main causes of ICT implementation failure (Aarts 2004;Lorenzi 1997;Pagliari 2005).…”
mentioning
confidence: 99%
“…With increasing computerisation in every sector of activity, ICTs are expected to become tools that are part of healthcare professional practice. Nonetheless, it appears that ICTs such as electronic medical records and the Internet remain underused by healthcare professionals (Berner 2005;Brooks 2006). Human and organisational factors have been identified as the main causes of ICT implementation failure (Aarts 2004;Lorenzi 1997;Pagliari 2005).…”
mentioning
confidence: 99%
“…9,10 Despite advocates' enthusiasm and the increasing availability of web-based clinical resources, there is evidence that the medical profession has been slow to adopt even the most basic IT tools. 11,12 Prior surveys of physician IT use have been limited to single practice settings (often academic centers) or single technologies (such as e-mail communication). [13][14][15][16][17][18][19][20][21][22] To more fully address the issue of basic IT adoption by physicians actively engaged in patient care, we surveyed a national sample of primary care and specialist physicians to determine frequency of e-mail communication with patients or with other providers, online access to continuing medical education (CME) programs or professional journal web sites, and ''realtime'' computerized decision support (CDS) during patient care.…”
mentioning
confidence: 99%
“…Berner et al (2005) (9) in their study showed that physicians believe that use of decision support systems and systems of prescribing medications can oppose their authority and independence. The results of previous studies have shown that many scientific advances, which have decreased the physicians' independence, have increased their resistance and opposition (9,20,28).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the main advantages of EHRs include increased knowledge about medical errors and attempts to decrease them, increased focus on patients' recovery, and improved quality of patient care (8). Although there has been significant progress in EHR around the world, it has not been fully implemented around the world during the past 3 decades, and it does not have the required effectiveness yet (9).…”
Section: Introductionmentioning
confidence: 99%